Experience of migraine, its severity, and perceived efficacy of treatments among cannabis users. (January 2021) - Gibson, Laurel P.; Hitchcock, Leah N.; Bryan, Angela D.; Bidwell, L. Cinnamon
Abstract: Objectives: As the legal and cultural landscape surrounding cannabis use in the United States continues to evolve, more Americans are turning to cannabis to self-medicate a number of ailments, including migraines. The purpose of the present study was to examine patterns of cannabis use and its associated relief among migraineurs. Design: Participants were N = 589 adult cannabis users living in states with full legal access. Using a cross-sectional design, participants completed an online survey assessing their cannabis use profiles, migraine experience, and self-reported relief from cannabis and non-cannabis treatments. Results: 161 participants (27.3 %) reported experiencing migraines. 76.4 % of migraineurs ( N = 123) endorsed using cannabis to treat their migraines. 69.9 % ( N = 86) of migraineurs using cannabis for migraine relief also endorsed using non-cannabis products (e.g., over-the-counter pain medication, triptans) to treat their migraines. Although their subjective health was similar ( p = .17), migraineurs who endorsed using cannabis to treat their migraines reported more severe migraines compared to those who did not ( p = .02). Migraineurs reported significantly more migraine relief from cannabis compared to non-cannabis products, even after controlling for migraine severity ( p = .03). The majority of migraineurs using cannabis to treat their migraines were not medical cardholders (65.0 %), suggesting that these individuals were self-medicating in lieu of physician guidance. Conclusions: The present study provides insight into the prevalence of cannabis use for migraine relief in a sample of cannabis users, and suggests that these migraineurs experience a high level of migraine relief from cannabis. Future studies are needed to determine the cannabis forms, potencies, and dosages that are most effective at treating migraine pain.